The size and destination of China's portfolio outflows - Rose M. Cunningham; Eden Hatzvi; Kun Mo (Bank of Canada, 2018)
The size of China's financial system raises the possibility that the liberalization of its capital account could have a large effect on the global financial system. This paper provides a counterfactual scenario analysis that estimates what the size and direction of China's overseas portfolio investments would have been in 2015 if China had had no restrictions on these outflows. In such a scenario, China's holdings of overseas portfolio assets would have been between US1.5 trillion and US3.2 trillion (13 to 29 per cent of Chinese GDP), or 5 to 12 times its actual holdings of US281 billion. Our model estimates that these additional holdings would have been predominantly directed to the world's deepest financial markets, especially the United States, while emerging-market economies would have received little additional portfolio investment. These results suggest that the liberalization of Chinese portfolio outflows may not prove disruptive to the global financial system, although it could have important implications for China.
Keywords: C23; F21; G15; F32; 330; Balance of payments and components; Econometric and statistical methods; International topics